Association Between Socioeconomic Deprivation and Functional Impairment After Stroke: The South London Stroke Register. Issue 3 (March 2015) - Chen, Ruoling; Crichton, Siobhan; McKevitt, Christopher; Rudd, Anthony G.; Sheldenkar, Anita; Wolfe, Charles D.A.
Abstract : Background and Purpose—: Previous findings of the association between socioeconomic deprivation and functional impairment after stroke are inconsistent. There is a lack of data on long-term association. We assessed the association and differences by age, sex, prestroke comorbidities, and stroke phenotypes. Methods—: We examined data from the South London Stroke Register cohort of 1995 to 2011, recording all first-ever strokes in patients of all ages in South London. A total of 2104 patients were alive at 3 months after stroke. Socioeconomic deprivation was measured using the index of multiple deprivation based on patient postcodes, and functional impairment after stroke was defined as a Barthel index of <15. Results—: At 3 months after stroke, 643 patients had functional impairment (30.6%; 95% confidence interval, 28.6%–32.5%). Compared with the first quartile of index of multiple deprivation (the least deprived), multivariate-adjusted odds ratios for functional impairment in patients with the second, third, and fourth quartiles were 1.29 (95% confidence interval, 0.94–1.76), 1.33 (0.97–1.82), and 1.78 (1.31–2.43), overall P =0.004. The association was significant in patients aged ≥65 years (corresponding odds ratios were 1.49 [1.02–2.17], 1.21 [0.83–1.75], and 1.94 [1.34–2.81]; P =0.003); in women, P =0.008, in patients who do not have prestroke comorbidities, P =0.009, and in patients with ischemic stroke, P <0.001, but not significant in their counterpart patients. There were similar patterns of the associations of socioeconomic deprivation with impairment at 3 years after stroke. Conclusions—: There are significant inequalities in short- and long-term functional recovery after stroke. General socioeconomic improvement, targeting groups at high risk of functional impairment is likely to reduce inequality in functional recovery after stroke. Abstract : Supplemental Digital Content is available in the text.